The Use of the Think-Pair-Share on Senior High School Students’ Mathematics Learning Achievement on Integral Concept - Kartini, Linda (Jurnal Pendidikan Indonesia Gemilang, 2023)
This study aimed to improve the ability of class XI high school students to understand the explanations of resource persons in mathematics by applying the Think Pair Share (TPS) learning model so that learning mathematics becomes more fun and creates creativity. The problem faced by the teacher is the need for students' ability to understand the speaker's explanation material, such as students' ability to understand definite integrals, calculate definite integrals and simple algebraic functions, and use integrals to calculate areas. This classroom action research was conducted in class XI in a school in Serang City, Banten. Activities carried out as many as two cycles of action. In general, the procedures in each action are (1) planning, (2) implementing, (3) observing, (4) reflecting on the results of action research, and the results show that based on data analysis during the cycle I and cycle II, it can be concluded that the application of the Think Pair learning model Share (TPS) in learning mathematics on integral material has increased both qualitatively and quantitatively, namely: The learning outcomes obtained by students in learning mathematics are: Initial results (pretest) show an average score: 46.75; The results in cycle I rose to an average score of: 77.25; The results in cycle II rose to an average score of 79.25. Student activity in carrying out mathematics learning activities shows: In cycle I, it shows an average of 60% (good enough), and in cycle II, it goes up and shows an average of 88% (very good). The results of the research and discussion above show that the action hypothesis is proven, namely, the use of the TPS model can improve mathematics learning outcomes for class XI high school students.